2021
DOI: 10.1177/09544089211040303
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on cutting factors of multi-layer machining for large aerospace thin-walled structural parts

Abstract: Large aerospace thin-walled structures will produce deformation and vibration in the machining process, which will cause machining error. In this paper, a cutting experimental method based on multi-layer machining is proposed to analyze the influence of cutting tool, cutting path, and cutting parameters on machining error in order to obtain the optimal cutting variables. Firstly, aiming at the situation that the inner surface of the workpiece deviates from the design basis, the laser scanning method is used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Agarwal and Desai 17 utilised a mechanistic cutting force model to estimate the induced cylindricity error during end milling of thin-walled circular components using finite element based framework and particle swarm optimisation algorithm. Yu et al 18 reported an experimental method based on multi-layer machining for obtaining optimum cutting parameters based on analysing the machining error. The development of comprehensive predictive and experimental methods that consider the structural deflections of the cutting tool/workpiece and the chatter instability requires further research effort to address the milling error challenge as reported in.…”
Section: Introductionmentioning
confidence: 99%
“…Agarwal and Desai 17 utilised a mechanistic cutting force model to estimate the induced cylindricity error during end milling of thin-walled circular components using finite element based framework and particle swarm optimisation algorithm. Yu et al 18 reported an experimental method based on multi-layer machining for obtaining optimum cutting parameters based on analysing the machining error. The development of comprehensive predictive and experimental methods that consider the structural deflections of the cutting tool/workpiece and the chatter instability requires further research effort to address the milling error challenge as reported in.…”
Section: Introductionmentioning
confidence: 99%